Highly strung ; Mother's milk ; Maniya Barredo [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
The drug story gets highlighted with the expose by Sen. Ernesto Herrera who names of drug lords and syndicates that protect the local trade. Advocates of mother's milk oppose mulit-national companies who sell powdered milk and encourage lactating mothers to use their products. Maniya talks about her life about ballerina.